Analysis Of The Correlation Background of Vocational Teacher’s Education With Teaching Professionalism And Student Achievement - Dame Ifa Sihombing; Ruth Mayasari Simanjuntak; Tutiarny Naibaho; Samuel Juliardi Sinaga (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to know: 1) the relationship between the background education of teachers of the vocational mining with student learning achievements, 2) the relationship of teaching professionalism with the learning performance of students, 3) the relation of background education teacher of the professional mining to the professionalism teaching. This is an expost-facto study. Research subjects of 45 SMK State and Private Pematangsiantar teachers. Data collection techniques using questionnaires. Data analysis techniques using correlation test analysis using SPSS 22.0 Research results: (1) there is a positive relationship between the educational background and the student’s learning performance of 24% and it is not significant that it is likely that the education background may not directly affect the students’ learning performance. It is expected that professional teachers to always improve the quality of teaching professionalism and pursue higher education.